Too much is too much?: Koros in ancient criticism and the poetics of scale - Grethlein, Jonas (TAPA, 2023)
The article explores the uses of κόρος (satiety, surfeit) in ancient criticism as part of a poetics of scale. It first shows that κόρος was applied to a wide range of different scales and used for an equally large array of phenomena. Then it suggests that Pindar's references to κόρος in Abbruchformeln (break-off formulas) may have been the origin of its later deployment by critics. Underneath the poetics of scale encapsulated in κόρος, it is finally argued, there is an entanglement of aesthetics with ethics that invites further inquiries.